Numerical Analysis of Nanofluids in Differentially Heated Enclosure Undergoing Orthogonal Rotation - H. Saleh; I. Hashim (Advances in Mathematical Physics)
Natural convection heat transfer in a rotating, differentially heated enclosure is studied numerically in this paper. The rotating enclosure is filled with water-Ag, water-Cu, water-Al2O3, or water-TiO2 nanofluids. The governing equations are in velocity, pressure, and temperature formulation and solved using the staggered grid arrangement together with MAC method. The governing parameters considered are the solid volume fraction, 0.0 ≤ ϕ ≤ 0.05, and the rotational speeds, 3.5≤ Ω ≤ 17.5 rpm, and the centrifugal force is smaller than the Coriolis force and both forces were kept below the buoyancy force. It is found that the angular locations of the local maximums heat transfer were sensitive to rotational speeds and nanoparticles concentration. The global quantity of heat transfer rate increases about 1.5%, 1.1%, 0.8%, and 0.6% by increasing 1% ϕ of the nanoparticles Ag, Cu, Al2O3, and TiO2, respectively, for the considered rotational speeds.